Indonesian Version of the Healthy Lifestyle Beliefs Scale for College Student: A Psychometric Study (Department of Physical Education, Sport, Health and Recreation, 2021)
The purpose of this study was to measure the healthy lifestyle beliefs by evaluating the validity and reliability of the healthy lifestyle belief scale in physical education students at Universitas Majalengka, West Java, Indonesia. The method used in the research is quantitative method with descriptive research type which was conducted on 106 physical education students from November 2020 to December 2020. Data collection was carried out using a google form which contains socio-demographic information and a healthy lifestyle belief scale. Cronbach’s Alpha and total item score analysis were used in the data analysis. Use Cronbach’s alpha to determine internal consistency of healthy lifestyle belief scales. The results showed that Cronbach’s alpha value was 0.968 and 16 items from the healthy lifestyle belief scale were normally distributed. The analysis showed 53% of the total variance. The healthy lifestyle belief scale for physical education students is a valid and reliable measurement tool and can be used as an instrument to develop relevant program interventions through physical education in schools and colleges.